Assistive technology (WIPO publication, 2021)
This groundbreaking report looks at patenting and technology trends in innovation in assistive technology. It identifies the prominent technologies, top players and markets for patent protection across seven domains - mobility, cognition, communication, hearing, the built environment, self-care and vision. Using a scale of technology readiness, it reveals which of the identified assistive products filed for patent protection are closest to commercialization. Este innovador informe analiza las tendencias tecnológicas y de patentes en la innovación en tecnología de asistencia. Identifica las tecnologías destacadas, los principales actores y los mercados para la protección de patentes en siete dominios: movilidad, cognición, comunicación, audición, entorno construido, cuidado personal y visión. Mediante el uso de una escala de preparación tecnológica, revela cuáles de los productos de apoyo identificados presentados para la protección de patentes están más cerca de la comercialización.